The Value of Groundwater Modeling to Support a Pump and Treat Design. Issue 3 (29th May 2013) - Compernolle, T.; Van Passel, S.; Lebbe, L.
Abstract A wide range of rules, algorithms, and models are available to design an effective pump and treat remediation system. Often, one refers to the effectiveness of the developed pump and treat system to demonstrate how valuable the use of a groundwater model can be. An economic valuation of the groundwater model is usually missing. This study provides a framework that puts the discussion concerning the use of groundwater models in an economic perspective. It is not only demonstrated that a more effective pump and treat system can be designed using a groundwater model, but also the economic implications of using a groundwater model are calculated. A set of economic decision rules is applied to determine the economic value of a groundwater model. It is shown that investing in a groundwater model can be economically worthwhile. The remediation time is reduced, remediation costs are saved and the property can be sold more early. These benefits outweigh the costs of developing a groundwater model, and hence a positive net benefit (NB) is determined.